2009
DOI: 10.1051/alr/2009042
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and seston quantity and quality effects on field reproduction of farmed oysters,Crassostrea gigas, in Bourgneuf Bay, France

Abstract: -The proliferation of the voluntarily-introduced cupped oyster, Crassostrea gigas, has attained the proportions of species invasion in many intertidal habitats in Europe, presumably resulting from successful reproduction of farmed individuals. It is thus imperative to better understand the reproductive characteristics of farmed oysters, since they are directly under human control. We quantified the dry tissue mass (DTM), gametosomatic index (GSI), and reproductive cycle of farmed oysters at two sites in Bourgn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 53 publications
0
33
0
1
Order By: Relevance
“…As a too high SPM concentration impacts oyster clearance rate and other physiological functions , oysters grown in this farming site are negatively impacted by high SPM concentration (Gernez et al, 2014). Daily mean chl a concentration was reported to vary between 4 and 14 mg m −3 (Dutertre et al, 2009), and monthly means between 5 and 30 mg m −3 were previously reported at the study site .…”
Section: Study Sitementioning
confidence: 67%
See 1 more Smart Citation
“…As a too high SPM concentration impacts oyster clearance rate and other physiological functions , oysters grown in this farming site are negatively impacted by high SPM concentration (Gernez et al, 2014). Daily mean chl a concentration was reported to vary between 4 and 14 mg m −3 (Dutertre et al, 2009), and monthly means between 5 and 30 mg m −3 were previously reported at the study site .…”
Section: Study Sitementioning
confidence: 67%
“…Enhanced characterization of the composition of the particulate assemblage could also be used to improve satellite-derived aquaculture products. For example, as oysters have the ability to preferentially select organic rather than mineral particles before ingestion Dutertre et al, 2009), estimation of the organic fraction of the particulate assemblage (Woźniak et al, 2010) could be used to better constrain shellfish physiological models.…”
Section: Shellfish Ecology From Space?mentioning
confidence: 99%
“…Typically, temperature peaks in summer and concentration of phytoplankton is generally higher during spring, summer and early autumn than in late autumn and winter (Gómez and Gorsky, 2003;Valiela and Cebrián, 1999). In these environments, most bivalve species display an annual reproductive cycle characterized by a resting period during the coldest months of the year with spawning inhibited under a given temperature threshold (Dutertre et al, 2009). During spring and summer, the most favorable period for gametogenesis and spawning, food availability has a major impact on spawning frequency and reproduction effort (Enríquez-Díaz et al, 2008;Mac Donald and Thompson, 1985;Ruiz et al, 1992;Saucedo et al, 2002;Saxby, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Stereological methods were used to determine volume fractions of different tissue types in the histological sections (Weibel et al 1966, Briarty 1975, Morvan & Ansell 1988, Pazos et al 1996, Mayhew 2000, Beninger et al 2001. For each section of the ovary, stereological counts were performed on 3 haphazardly-chosen areas using a 10 × 10 point matrix on the microscope screen at 100 ×, as described in Dutertre et al (2009). In females, 6 tissue categories were counted: developing oocytes, mature oocytes, oocytes undergoing atresia, lysed oocytes, unoccupied tubule space, and inter-tubular space.…”
Section: Specimen Sampling Histological Preparation and Reproductivementioning
confidence: 99%
“…Normal C. gigas spawning in Bourgneuf Bay occurs from May to July (Dutertre et al 2009(Dutertre et al , 2010, so the appearance of C. fornicata larvae as early as February would permit the benthic recruitment of this species well in advance of C. gigas (which spawned in The combined effect of both an extended brooding season and increased propagule numbers may be expected to accentuate the proliferation of Crepidula fornicata in Bourgneuf Bay, and by the same token, provide a competitive advantage to this species with respect to the co-occurring Crassostrea gigas.…”
Section: Reproductive Cyclesmentioning
confidence: 99%